Faktor-Faktor yang Mempengaruhi Permintaan Sayuran Hidroponik di Kota Pekanbaru - Olga Kusuma, Fauziah; Tety, Ermi; Edwina, Susy (Universitas Jambi, 2023)
Hydroponics is one of the cultivation technologies that is able to produce products with good quality. The specialty of hydroponic vegetables has attracted consumers to consume these products so that demand arises. This study aims to (1) analyze the factors that affect the demand for hydroponic vegetables in Pekanbaru City, and (2) analyze the elasticity of hydroponic vegetable demand in Pekanbaru City. The study was conducted in 4 modern markets spread across Pekanbaru City with a total sample of 40 respondents with purposive sampling method. The analysis used in the study was multiple linear log regression analysis. The results showed that (1) factors that significantly affect the demand for hydroponic vegetables are the price of hydroponic vegetables, household income, consumer knowledge, and lifestyle with a coefficient of determination (R2) value of 86.60 percent.Â (2) The demand for hydroponic vegetables is inelastic to the price of the goods themselves, the price of other goods, and income so that hydroponic vegetables include normal goods and substitutions.